2019
DOI: 10.1016/j.pmedr.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of health literacy with utilization of health-care services in a general Japanese population

Abstract: Many studies have explored the association between health literacy and health-care utilization; however, the majority assessed functional health literacy in terms of basic skills. Japan's health-care and medical examination system in workplaces is different from that of other major countries. This study examined the relationship of health literacy with health-care use (emergency visit, hospitalization, dental checkup, and health checkup or cancer screening); it focused on differences by occupation and health-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 34 publications
3
46
0
6
Order By: Relevance
“…Previous studies that measured HL among the Japanese general population ( Ishikawa et al, 2008 , Ishikawa et al, 2016 , Goto et al, 2019 ) have reported an average CCHL score ranging from 3.59 to 3.72. Since the average score for respondents in this study was 3.11 ± 0.81, it appears that the HL of Fukushima Prefecture residents is relatively lower than that of the other population in Japan.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies that measured HL among the Japanese general population ( Ishikawa et al, 2008 , Ishikawa et al, 2016 , Goto et al, 2019 ) have reported an average CCHL score ranging from 3.59 to 3.72. Since the average score for respondents in this study was 3.11 ± 0.81, it appears that the HL of Fukushima Prefecture residents is relatively lower than that of the other population in Japan.…”
Section: Discussionmentioning
confidence: 97%
“…Future research should also consider updating the validated instrument used in the present study to include questions on any new factors related to routine checkups identified in the literature since this study was undertaken. For example, a recent study found a significant association between health literacy and use of health checkup among Japanese population [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, we measured HL with a validated questionnaire, and categorized the HL scores into lower and higher HL groups in a manner consistent with the validation study (Ishikawa et al, 2008). Although the original validation study included only Japanese male office workers (Ishikawa et al, 2008), several studies have used this scale for both men and women (Goto et al, 2019; Ishikawa et al, 2018; Yokokawa et al, 2016). Therefore, we considered this HL scale was applicable for participants in our study.…”
Section: Discussionmentioning
confidence: 99%